Ultrasound inhibits tumor growth and selectively eliminates malignant brain tumor in vivo - Nitsa Buaron; Antonella Mangraviti; Yuan Wang; Ann Liu; Mariangela Pedone; Eric Sankey; Itay Adar; Abraham Nyska; Riki Goldbart; Tamar Traitel; Henry Brem; Betty Tyler; et al. (Wiley, 2024)
Abstract Glioma is one of the most common primary malignant brain tumors. Despite progress in therapeutic approaches, the median survival of patients with glioma remains less than 2 years, generating the need for new therapeutic approaches. Ultrasound (US) is widely used in medical fields and is used as a therapeutic tool mainly for improving the performance of therapeutic entities. In this study, we examined a novel approach using low frequency US (20 kHz) (LFUS) as an independent treatment tool for malignant glioma, since primary studies showed that cancer cells are more susceptible to LFUS than healthy cells. LFUS safety and efficacy were examined in a 9L gliosarcoma‐bearing female Fischer 344 rats. Two LFUS protocols were examined: a one‐time treatment (US1X), and two treatments 24 h apart (US2X). For safety evaluation, rats were monitored for weight change and pain measurements. For efficacy, tumor volume was measured as a function of time and the tumor structural chances were examined histopathologically. LFUS treatment showed rapid inhibition of tumor growth, seen as soon as 12 h after US application. In addition, LFUS was found to affect the tumor structure, which was more extensive (>60% of tumor area) in smaller tumors. In US2X, the tumor tissue was completely destroyed, and an extensive immune response was observed. Importantly, the treatment was highly selective, keeping the healthy tissue surrounding the tumor unharmed. We developed a highly efficient and selective therapeutic protocol for treating malignant glioma with minimal side effects based solely on LFUS.